Assembly-Line Balancing under Demand Uncertainty - Stall Sikora, Celso Gustavo (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2022)
Assembly lines are productive systems, which are very efficient for homogeneous products. In the automotive industry, an assembly line is used in the production of several vehicle variants, including numerous configurations, options, and add-ins. As a result, assembly lines must be at the same time specialized to provide high efficiency, but also flexible to allow the mass customization of the vehicles. In this book, the planning of assembly lines for uncertain demand is tackled and optimization algorithms are offered for the balancing of such lines. Building an assembly line is a commitment of several months or even years, it is understandable that the demand will fluctuate during the lifetime of an assembly line. New products are developed, others are removed from the market, and the decision of the final customer plays a role on the immediate demand. Therefore, the variation and uncertainty of the demand must be accounted for in an assembly line. In this book, methods dealing with random demand or random production sequence are presented, so that the practitioners can plan more robust and efficient production systems. About the author Celso Gustavo Stall Sikora is an industrial engineer and was a research assistant at the Institute for Operations Research at the University of Hamburg where he received his PhD in 2021. His work focus on optimization procedures for the design and operation of automotive production systems.
Introduction -- Design and operation of assembly lines -- Literature review on assembly line balancing under uncertainty -- Balancing under full sequencing control -- Balancing under no sequencing control -- Controlling production sequences using buffers -- Conclusion.
Keywords: Operations research; Operations Research and Decision Theory